QIROAH LEARNING ASSISTANCE FOR MTS MA'ARIF WALISONGO 2 STUDENTS KRANDEGAN HAMLET, SUKOMAKMUR VILLAGE, KAJORAN DISTRICT - Rezky Idris (khidmatan, 2023)
MTS Ma’arif Walisongo 2 is the only nonformal educational institution in Krandegan hamlet, Sukomakmur Village, Kajoran sub-district, Magelang district. This institution is the center of a school teaching reading the Al-Qur'an from an early age in the hamlet. However, there are deficiencies at the school. Namely, a few MTS Ma’arif Walisongo 2 st students have entered the Qiro’ah field. The students all read the Al-Qur'an in the usual tone. The purpose of this activity is to provide students with understanding and learning in order to be able to read the Qur’an by applying the Qiro’ah rules. In this activity, the servant meets the students face to face. The result of this dedication is an increase in reading the Qur’an properly and correctly, supported by an understanding of the Al-Qur'an Science material. The approach method is the Asset Based Community Development (ABCD) method, which focuses on asset development.